Structural Balances and All That : Which Indicators to Use in Assessing Fiscal Policy - Chalk, Nigel (IMF Working Papers; Working Paper ;, 2002)
Structural indicators of a country's fiscal position are regularly used as estimates of both discretionary changes in fiscal policy and the effect of fiscal policy on aggregate demand. This paper looks at such indicators and evaluates, from a theoretical standpoint and from empirical case studies, their usefulness in measuring the size of discretionary policy action or fiscal demand stimulus. Two propositions are examined in detail: first, that the change in the primary structural balance provides a better indicator of discretionary fiscal policy than does the change in the primary balance; and second, that the change in the structural balance is a good indicator of the demand stimulus arising from changes in the fiscal position. In addition, the paper discusses measurement problems relating to structural balances and the use of the fiscal impulse as an alternative to structural balances.